Experimental and analytical assessment of fatigue and crack propagation in cold worked open hole specimens. Issue 9 (30th April 2013) - Boni, L.; Fanteria, D.; Lanciotti, A.; Polese, C.; Susmel, L.; Iacoviello, F.; Ferro, G.
ABSTRACT Fatigue and crack propagation tests are carried out on 7075‐T73 open hole aluminium alloy specimens. A remarkable increment of fatigue life due to the Split Sleeve Cold ExpansionTM process is observed, further improved by applying the process twice on the same hole. Comparable increments are obtained by using the StressWaveTM method. Specific tests are performed in order to point out a possible relaxation of the residual stresses due to fatigue loading. The results obtained reveal no relaxation phenomena in the tested specimens. The compressive residual stress around cold expanded holes is numerically evaluated. Dedicated experiments based on the Sachs method are conducted to confirm the residual stress prediction.